Case report: Creutzfeldt-Jakob disease presenting with anxiety symptoms in a COVID-19 post-infection patient - Yong, Christl S. K.; Maniam, Ethan Jian-Hui; Chang, Cheryl W. L.; Lai, Jonathan Yexian; Ho, Cyrus Su Hui (Frontiers in Neurology, 2023)
Creutzfeldt-Jakob Disease (CJD) is a rare, rapidly progressive, and fatal neurodegenerative disorder. We describe a man whose initial manifestations of CJD occurred shortly after contracting Coronavirus disease 2019 (COVID-19). He first developed anxiety and short-term memory loss a few weeks after a mild COVID-19 infection. He subsequently developed parkinsonism, eventually progressed to akinetic mutism, and passed away 5 months after symptom onset. This case highlights a potential temporal relationship between COVID-19 infection and the onset of neurodegenerative symptoms. Microglia and astrocytes in the central nervous system (CNS) and ‘S1’ spike proteins on SARS-CoV-2 are potential mediators in neuroinflammation and neurodegeneration.